An integrative review of management research on caste: Broadening our horizons - BAPUJI, Hari (Institutional Knowledge at Singapore Management University, 2024)
Even though management research on caste is growing, it is not yet on a clear trajectory to realize its vast potential due to varying terminology and framing of caste, the limited incorporation of directly relevant work from proximate disciplines, and the narrow and selective usage of the attributes of caste. To remove these obstacles, we review 259 scholarly works on caste (216 articles and 43 books and research reports) and develop an integrative framework to i) clarify the contemporary manifestations of caste as being a graded hierarchy, an inherited membership, and a set of socially enforced practices, and ii) summarize the outcomes of caste at individual, occupational, organizational, and societal levels, while also consolidating the mechanisms through which caste influences these outcomes. Additionally, to position management scholarship on this topic for greater impact, we develop a research agenda that reflects contemporary interests in management and the world at large about inclusion in organizations and societies. The caste system has practical significance for a large portion of the global population.